2017
DOI: 10.1186/s13073-017-0454-9
|View full text |Cite
|
Sign up to set email alerts
|

Detecting protein variants by mass spectrometry: a comprehensive study in cancer cell-lines

Abstract: BackgroundOnco-proteogenomics aims to understand how changes in a cancer’s genome influences its proteome. One challenge in integrating these molecular data is the identification of aberrant protein products from mass-spectrometry (MS) datasets, as traditional proteomic analyses only identify proteins from a reference sequence database.MethodsWe established proteomic workflows to detect peptide variants within MS datasets. We used a combination of publicly available population variants (dbSNP and UniProt) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 49 publications
1
55
0
Order By: Relevance
“…Mirror Protease Strategy for Precision De Novo Sequencing on Long Peptides-Previous studies have reported that the ion coverage negatively correlated with the length of peptides, which indicates a challenge to sequence long peptides (11,44,45). We investigated the impact of peptide length on de novo sequencing.…”
Section: Near-complete Ion Coverage From the Complementary Effects Ofmentioning
confidence: 99%
“…Mirror Protease Strategy for Precision De Novo Sequencing on Long Peptides-Previous studies have reported that the ion coverage negatively correlated with the length of peptides, which indicates a challenge to sequence long peptides (11,44,45). We investigated the impact of peptide length on de novo sequencing.…”
Section: Near-complete Ion Coverage From the Complementary Effects Ofmentioning
confidence: 99%
“…Top-down mass spectrometry allows for the determination of amino acid sequences and their PTMs without first digesting proteins into peptides. This provides more precise compositional information and adds molecular details which are typically lost when proteins are first digested into peptides as done in bottom-up proteomics [22,159] (Figure 3 (a-b)). Mass spectrometry of complete proteins is the most optimal method to detect de novo proteoforms with complex PTM patterns [6].…”
Section: Top-down Proteomicsmentioning
confidence: 99%
“…It is essential to understand the connection between genomic sequence and proteomic activity when trying to develop effective treatments [129,168,169]. Furthermore, this sample specific approach utilizing custom search databases has shown lower false-positive and false-negative rates making mass spectrometry data increasingly reliable [159].…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…Likewise, Alfaro et al. combined publicly available variants (dbSNP and UniProt) and somatic variations in cancer (COSMIC); along with sample‐specific genomic and transcriptomic data to examine proteome variation in 59 NCI60 cancer cell‐lines, resulting in the identification of 7.3 million novel variant peptides and 4771 mutations . In a separate study, Zhang et al.…”
Section: Applications Of Proteogenomics In Biologymentioning
confidence: 99%